Analisis Harga Dan Kualitas Beras Terhadap Permintaan Konsumen Di Pasar Gisting - Dedi Wahyudi; Meiria Murphi; Qomaruz Zaman (Dinar Islamic Review, 2020)
The purpose of this study was to determine the effect of rice quality and price on rice demand. This research is a descriptive type, namely research that describes objects related to rice demand. The population in this study were all who bought rice at the gisting market and the sample taken was 30 people who bought rice at the gisting market, which were taken intentionally and who were willing to be interviewed. The data collection is done by using a questionnaire. The results of multiple linear regression analysis from the results of calculations using the IBM SPSS program are known that the influence of rice quality and price on consumer demand has a significant effect with R = 0.355 which means 35.5% of rice price and quality variables affect consumer demand, while the rest is influenced by other variables not examined in this study. Then for ri obtained 0.126 which means the level of closeness of the relationship between price and quality of rice to demand is 12.6% which means low. The value of the coefficient of determination is 0.061 or 6.1%, which means that x can explain y only by 6.1%.